PREVENTING AND FIGHTING CORRUPTION THROUGH PUBLIC POLICIES - Dr. Drs. H. Dudu Duswara Machmudin S.H., M.Hum. (UNTAG Law Review, 2018)
Law enforcement does not engage in a vaccum space, yet it is related tovariables of socio-political condition, mental of the law enforcers, criminal lawprocedures, law ideology, NGOs, and legal awareness of the society. Moreover,fighting corruption through law enforcement demands collective awareness asstakeholders to actively participate in national efforts to prevent and eradicatecorruption. Measures taken on the prevention must be built in socio-political climateand national collective culture which enforce zero tolerance to any forms of corruption, including bribery, gratification, trading influence, illicit enrichment, corporate corruption, political corruption, collusion, and nepotism.